The Key Drivers of Poverty in Sub-Saharan Africa and What Can Be Done About it to Achieve the Poverty Sustainable Development Goal - Anyanwu, John C; Anyanwu, Joanna C (Asian Journal of Economic Modelling, 2017)
The first Sustainable Development Goal targets ending poverty in all its forms everywhere by 2030. And one of the most remarkable achievements during the MDG era was the significant decline in the share of the extremely poor in the global population, leading to the global attainment of cutting the extreme poverty rate to half its 1990 level by 2015. However, Sub-Saharan Africa remained the only developing region where the MDG 1 target was not achieved. Based on the updated poverty line of $1.90 a day, poverty reduction in Sub-Saharan Africa significantly lags other developing regions. Understanding the key drivers and ways of tackling poverty in Sub-Saharan Africa becomes one of the pressing development challenges of our time. Our empirical estimates for the period, 1980 to 2013, show that the key factors significantly feeding poverty incidence and poverty depth in the region include high income inequality, oil-dependence, institutionalized democracy, high prevalence of HIV among the female youth, and increased civil war episodes. On the other hand, the key drivers significantly reducing poverty in the region are higher levels of economic development (income per capita), higher general government final consumption expenditure, higher official development assistance and aid received, urbanization, and access to improved water source. The policy implications are discussed.